Zonder vrienden geen carrière. De succesvolle loopbanen van de zeventiende-eeuwse kunstenaars Govert Flinck en Ferdinand Bol - Kok, Erna (De Zeventiende Eeuw: Cultuur in de Nederlanden in interdisciplinair perspectief, 2012)
At his arrival (1633) in the unfamiliar city of Amsterdam, Govert Flinck was assured of the support of affluent relatives as well as of the networks of both Rembrandt and the art dealer Uylenburg. The stylistically adaptable Flinck was an active networker and obtained both an honourable position as a friend and success as a painter in the network of eminent magistrates. Ferdinand Bol also chose Rembrandt as master, but lacked support by relatives. Still, through his marriage with Elysabeth Dell (1652) he achieved a solid position in the networks of the admiralty and magistrates, which gained him continued commissions. His second marriage to Anna van Erckel (1669) offered him the opportunity to refrain from painting.